2015
DOI: 10.1017/thg.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Etiology of the Relationship Between Childhood Hyperactivity/Inattention and Conduct Problems in a South Korean Twin Sample

Abstract: Recently, there has been increased research into the etiology of the comorbidity between hyperactivity/inattention problems (HIP) and conduct problems (CP). However, the nature of the etiology of the comorbidity has remained unclear. Mothers of 507 pairs of twins, comprised of 221 monozygotic (MZ) and 286 dizygotic (DZ) twin pairs aged from 6 to 13 years (mean = 9.6 years; SD = 2.0 years), completed the HIP and the CP scale of the Strengths and Difficulties Questionnaire (SDQ) via a telephone interview. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In the best-fitting model (Model 6, Figure 2), additive genetic and unique environmental variance components were, respectively, 0.10 [95% CI: 0.04–0.34] and 0.61 [95% CI: 0.51–0.71] for CP, and 0.51 [0.40–0.60] and 0.49 [0.40–0.60] for NE; shared environmental variance, 0.29 [0.09–0.36] was significant only for CP; and additive genetic and unique environmental correlations between NE and CP were 1.0 [0.49–1.00] and 0.37 [0.26–0.47], respectively. A significant amount of shared environmental influences on CP was in agreement with other twin studies of CP based on early adolescents (Burt, 2009) and a prior study based on a subsample of the present study (Hur, 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the best-fitting model (Model 6, Figure 2), additive genetic and unique environmental variance components were, respectively, 0.10 [95% CI: 0.04–0.34] and 0.61 [95% CI: 0.51–0.71] for CP, and 0.51 [0.40–0.60] and 0.49 [0.40–0.60] for NE; shared environmental variance, 0.29 [0.09–0.36] was significant only for CP; and additive genetic and unique environmental correlations between NE and CP were 1.0 [0.49–1.00] and 0.37 [0.26–0.47], respectively. A significant amount of shared environmental influences on CP was in agreement with other twin studies of CP based on early adolescents (Burt, 2009) and a prior study based on a subsample of the present study (Hur, 2015).…”
Section: Resultssupporting
confidence: 93%
“…A = additive genetic influences, E1 = unique environmental influences and measurement error specific to Negative Emotionality, E2 = unique environmental influences and measurement error specific to Conduct Problems. (Burt, 2009) and a prior study based on a subsample of the present study (Hur, 2015). Taken together, the parameter estimates in the bestfitting model for older children suggested that 53% (r = 0.23; 1.0 × Ý.10 × Ý.51) of the phenotypic correlation of 0.43 between CP and NE were attributable to correlated additive genetic factors, and the remainder, 47% (r = 0.20; 0.37 × Ý.61 × Ý.49, to correlated unique environmental factors.…”
Section: Younger Groupmentioning
confidence: 80%
“…The Standard Progressive Matrices-Plus version (Raven, 2008) has been used for assessment of cognitive abilities for school-aged twins. To measure problem behaviors and mental health traits, the Strengths and Difficulties Questionnaire (Goodman, 1997), hostility (Koskenvuo et al, 1988), Launey-Slade Hallucination Scale -Revised (Launay & Slade,1981), clinical symptoms of Personality Assessment Inventory (Morey, 1991), Center for Epidemiological Studies-Depression scale (Radloff, 1977), and Maudsley Obsessive-Compulsive Inventory (Hodgson & Rachman, 1977), and hwabyung (anger syndrome), have been administered to adolescent and young adult twins (Hur, 2006(Hur, , 2007b(Hur, , 2008(Hur, , 2009b(Hur, , 2014(Hur, , 2015Hur et al, 2015;Hur, Cherny et al, 2012;Hur, Choi et al, 2018;Hur & Jeong, 2008;Hur & Rushton, 2007). To assess physical and psychological family environment, the Family Asset Questionnaire and the Family Adaptability and Cohesion Scale (Olson et al, 1985) have been administered to twins or parents of twins.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the etiology of the association between aggression and ADHD indicated that these associations were largely explained by pleiotropic genetic factors. Hur (2015) presented a review of twin studies on hyperactivity/inattention and Conduct Problems, which showed moderate to high (0.17-0.68) phenotypic correlations, and high genetic correlations (0.43-1.0). Based on a systematic review, Andersson et al (2020) reported a genetic correlation between externalizing symptoms and ADHD of 0.49 (CI 0.37-0.61).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%